2019
DOI: 10.1002/slct.201901948
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene Based NLOphoric D‐π‐A‐π‐D Coumarin‐Chalcone and Their Red Emitting OBO Difluoride Complex: Synthesis, Solvatochromism, Z‐scan, and Detailed TD‐DFT Studies

Abstract: NLOphoric D-π-A-π-D coumarin chalcone 5 and their BF 2 complex 6 were designed, synthesized and characterized through Mass, 13 C-NMR, and 1 H-NMR analysis. Their Photophysical properties are extensively studied in solvents of different polarity. On BF 2 complexation of coumarin chalcone shows highly red shift in absorption and emission spectra compared to uncomplexed coumarin chalcone. Positive solvatochromism observed which is well supported by linear and multilinear regression analysis. For BF 2 complexed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 111 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…The theoretically observed values of first‐order hyperpolarizability (β) and second‐order hyperpolarizability (γ) for 2‐napthol azo dyes 1–4 are larger than the values for hyperpolarizability of urea . Moreover, the β and γ values of these dyes were compared with the reported donor‐π‐acceptor dyes . We found that β and γ values of these dyes are competes with the reported donor‐π‐acceptor dyes supplementary information (Table S30).…”
Section: Resultsmentioning
confidence: 83%
“…The theoretically observed values of first‐order hyperpolarizability (β) and second‐order hyperpolarizability (γ) for 2‐napthol azo dyes 1–4 are larger than the values for hyperpolarizability of urea . Moreover, the β and γ values of these dyes were compared with the reported donor‐π‐acceptor dyes . We found that β and γ values of these dyes are competes with the reported donor‐π‐acceptor dyes supplementary information (Table S30).…”
Section: Resultsmentioning
confidence: 83%
“…In this regard, several coumarin-based dyes have been reported over the last decades (Figure 1), and significant efforts have been devoted to the analysis, understanding, and optimization of their photophysical properties [3,11,12]. [13], ii [14], iii [15], iv [16], v [17], vi [18], vii [19], viii [20], ix [21].…”
Section: Introductionmentioning
confidence: 99%
“…The rule of thumb in the molecular design of coumarin-based dyes is that the introduction of electron-donating groups (EDG) at positions 6 or 7 (e.g., -OH, -NRR') and electron-withdrawing groups (EWG) at positions 3 or 4 (e.g., -CF3, -COOR, -CN) results in a redshift of the absorption and the emission maxima, due to the existence of a strong intramolecular charge transfer (ICT) process along the coumarin backbone [3]. Extending the π-conjugation system via the fusion of polymethine groups [17] or bulky aromatic scaffolds (e.g., pyrene [18,22], hemicyanine [21,[23][24][25], or BODIPY [20,26,27]) through position 3 is another common strategy to redshift the absorption and [13], ii [14], iii [15], iv [16], v [17], vi [18], vii [19], viii [20], ix [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation